Foam Cells Control Mycobacterium tuberculosis Infection - Agarwal, Pooja; Combes, Theo W.; Shojaee-Moradie, Fariba; Fielding, Barbara; Gordon, Siamon; Mizrahi, Valerie; Martinez, Fernando O. (Frontiers in Microbiology, 2020)
Mycobacterium tuberculosis (Mtb) infects macrophages and macrophage-derived foam cells, a hallmark of granulomata in tuberculous lesions. We analysed the effects of lipid accumulation in human primary macrophages and quantified strong triglyceride and phospholipid remodelling which depended on the dietary fatty acid used for the assay. The enrichment of >70 percent in triglyceride and phospholipids can alter cell membrane properties, signalling and phagocytosis in macrophages. In conventional macrophage cultures, cells are heterogeneous, small or large macrophages. In foam cells, a third population of 30 percent of cells with increased granularity can be detected. We found that foam cell formation is heterogenous and that lipid accumulation and cell formation reduces the phagocytosis of Mtb. Under the conditions tested, cell death was highly prevalent in macrophages, whereas foam cells were largely protected from this effect. Foam cells also supported slower Mtb replication, yet this had no discernible impact on the intracellular efficacy of four different antitubercular drugs. Foam cell formation had a significant impact in the inflammatory potential of the cells. TNF-α, IL-1β and prototypical chemokines were increased. The ratio of inflammatory IL-1β, TNF-α and IL-6 versus anti-inflammatory IL-10 was significantly higher in response to Mtb versus LPS, and was increased in foam cells compared to macrophages, suggestive of increased pro-inflammatory properties. Cytokine production correlated with NF-κB activation in our models. We conclude that foam cell formation reduces the host cell avidity for, and phagocytosis of, Mtb while protecting the cells from death. This protective effect is associated with enhanced inflammatory potential of foam cells and restricted intracellular growth of Mtb.